Hollow Palaces An Anthology of Modern Country House Poems. - Gardner, Kevin (Liverpool University Press, 2021)
This unique gathering of poems about country houses from Hardy to Armitage is more than just a highly entertaining anthology of accessible modern verse. It amounts to a survey of politico-historical shifts in twentieth-century British society as seen and imagined by both insiders and outsiders. It is the first such anthology.